2012
DOI: 10.1111/j.1743-6109.2011.02553.x
|View full text |Cite
|
Sign up to set email alerts
|

The Female Sexual Function Index: Translation and Validation of an Iranian Version

Abstract: Introduction Female sexual dysfunction (FSD) is a prevalent problem in the female population in Iran. A subjective assessment instrument that allows cross-cultural comparison of FSD is urgently needed. Aim The aims of the study were to translate, validate, and enhance cross-cultural comparability of an Iranian version (IV) of the Female Sexual Function Index (FSFI)—the IV-FSFI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
133
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(145 citation statements)
references
References 43 publications
11
133
0
1
Order By: Relevance
“…Consequently, a score lower than 3.9 in each of the FSFI domains was considered sexual dysfunction (11). The findings of numerous validation studies have shown that the FSFI has satisfactory reliability and validity indices (23)(24)(25)(26)(27). Reliability and validity of the Iranian version of FSFI was assessed in Iran (26,27).…”
Section: Selection Of Study Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, a score lower than 3.9 in each of the FSFI domains was considered sexual dysfunction (11). The findings of numerous validation studies have shown that the FSFI has satisfactory reliability and validity indices (23)(24)(25)(26)(27). Reliability and validity of the Iranian version of FSFI was assessed in Iran (26,27).…”
Section: Selection Of Study Subjectsmentioning
confidence: 99%
“…The findings of numerous validation studies have shown that the FSFI has satisfactory reliability and validity indices (23)(24)(25)(26)(27). Reliability and validity of the Iranian version of FSFI was assessed in Iran (26,27). Internal consistency was evaluated using Cronbachalpha coefficient in each of the six domains of the scale.…”
Section: Selection Of Study Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 The Iranian version of the FSFI has been found to be a valid and highly reliable tool for detecting sexual dysfunction among women. 9 …”
Section: Fsfimentioning
confidence: 99%
“…[4][5][6][7][8] Female sexual dysfunction (FSD) can often interfere with quality of life. 9 Studies have found that women with SCI believe that they should have a passive role during sexual intercourse and this adversely affects their sexual functioning. 7 In a previous study that explored sexual dysfunction in females with SCI, 8 Lombardi and collogues investigated FSD using the Female Sexual Function Index (FSFI).…”
Section: Introductionmentioning
confidence: 99%